The Diatoms in four Postglacial deposits at Godthåbsfjord, West Greenland. - Foged, Niels (Meddelelser om Grønland, 1977)
A core from the bottom of each of four lakes in the region of Godthåbsfjord, western Greenland, is examined for content of diatoms. It is shown that all the lakes came into existence during the postglacial upheaval, the nethermost part of the 4 cores consisting of marine sediment and the remainder part being freshwater material. The diatoms found are listed according to their halobion and pH-relation, and the result is summed up in halobion and pH-spectra. The development of pH to the lakes from their start up to now is illustrated by means of diagrams. Two new species are described: Achnanthes fredskildii and Achnanthes iversenii, and one forma nova: Neidium iridis fo. crassiusculum. In addition 8 plates with photos of a total of 106 taxa are given.